The Classroom Communication Resource (CCR) intervention to change grade 7 peers' attitudes towards children who stutter (CWS) in the Western Cape: a randomised controlled trial - Mallick, Rizwana (Department of Health and Rehabilitation Sciences, 2019)
Background: There is an established need to manage teasing and bullying of children who stutter (CWS) through changing the attitudes of their peers. The intervention, the Classroom Communication Resource (CCR), was implemented by teachers in classrooms. The primary objective of the main study was to determine the effectiveness of the CCR through a cluster Randomised Controlled Trial (RCT). The secondary objective of this study was to determine the treatment effect of the Stuttering Resource Outcomes Measure (SROM) within the subscales of Positive Social Distance (PSD), Social Pressure (SP) and Verbal Interaction (VI). The subgroup objective was to determine the primary objective between and across lower and higher school quintile clusters. Method: A cluster RCT was conducted. Participants in grade 7, aged 11 years and older, were randomly assigned to control and intervention groups using school and subgroup (quintile) clusters classifications. Following randomisation, stratification took place using a 1:1 allocation ratio. Participants viewed a video of a child who stuttered at baseline. Teachers administered the CCR (social story, role-play, discussion) in intervention groups only over a 60-90 minute session after they received an hour of training. Peer attitudes were measured at baseline and at 6 months post-intervention using the SROM in intervention and control groups. Results: A total of 10 schools were included whereby they were randomly allocated to control (k=5) and intervention groups (k=5). Within the schools, 454 participants were included with n =223 participants in the intervention and n= 231 in the control group. The study showed no statistically significant difference on the global SROM score (mean difference: -0.11 [95% confidence interval: -1.56, 1.34]; p = 0.88). Similarly, no significant differences were noted on SROM subscales: PSD (1.04 [-1.02,311]; p =0.32), SP (-0.45 [-1.22, 0.26]; p=0.21) and VI (0.05 [-1.01, 1.11]; 0.93), the secondary objective of this study. No significant subgroup effect on the global SROM score (lower vs higher quintile subgroups) [interaction p-value = 0.52] was observed during subgroup analysis. Results were however consistent with the hypothesis and quintile subgroups behaved similarly. Results were found clinically important when considering confidence intervals as well as the magnitude and direction of treatment effect. Conclusion: While the treatment effect showed no statistically significant differences on the global SROM and within the constructs of PSD, SP and VI, a clinically important result was noted when evaluating the meaningfulness of this study as well as its implications. Subgroup analysis showed that the quintiles behaved similarly, showing that the CCR was appropriate for schools within the lower and higher quintiles.